BEYOND BORDERS: STRATEGI INDONESIA DALAM MEWUJUDKAN HAK PENGUNGSI DI SELA-SELA KONVENSI - Luqman Hakim; Erna Setijaningrum; Ramadhany Nugroho (ITB AAS Indonesia Surakarta, 2024)
Abstract This research evaluates Indonesia's strategy in respecting refugee rights, particularly through the policy implementation of the Task Force for Foreign Refugee Handling (Satgas PPLN) in Sidoarjo, in response to challenges arising from not ratifying the 1951 Refugee Convention. A qualitative methodology was employed for an in-depth exploration of phenomena within their real-life context, including extensive interviews with stakeholders directly involved in refugee management, field observations at refugee accommodations like Puspa Agro Apartment and Hotel Green Bamboo, and document analysis including government regulations and reports from UNHCR and IOM. Findings reveal Indonesia’s strategic engagement in fulfilling basic human rights for refugees, such as shelter and healthcare, while facing challenges in non-formal work participation and the absence of formal education and work permits for refugees. Through the establishment of Satgas PPLN and collaboration with international bodies, Indonesia demonstrates a commitment to humanitarian principles, despite legal and economic framework limitations. This study concludes that Indonesia’s approach contributes to the global discourse on refugee management by showcasing how a country can engage in refugee protection without being bound by international refugee convention laws. It highlights the importance of local initiatives and international cooperation in addressing refugee needs and suggests the necessity for more inclusive policies facilitating social and economic integration of refugees. Practical implications include recommendations for enhanced surveillance and investigation to prevent refugee exploitation by smuggling syndicates and the dissemination of legal information to refugees to reduce illegal entry and stay. Keywords: immigration, collaborative governance, refugees, UNHCR Abstrak Penelitian ini mengevaluasi strategi Indonesia dalam menghormati hak pengungsi, khususnya melalui implementasi kebijakan Satgas PPLN di Sidoarjo, sebagai respons terhadap tantangan yang muncul akibat tidak meratifikasi Konvensi Pengungsi 1951. Metodologi kualitatif digunakan untuk eksplorasi mendetail fenomena dalam konteks kehidupan nyatanya, meliputi wawancara mendalam dengan pemangku kepentingan yang langsung terlibat dalam manajemen pengungsi, observasi lapangan di akomodasi pengungsi seperti Apartemen Puspa Agro dan Hotel Green Bamboo, dan analisis dokumen termasuk regulasi pemerintah dan laporan dari UNHCR dan IOM. Temuan mengungkapkan keterlibatan strategis Indonesia dalam memenuhi hak dasar manusia bagi pengungsi, seperti tempat berlindung dan perawatan kesehatan, tantangan partisipasi kerja non-formal dan absennya pendidikan formal serta izin kerja untuk pengungsi. Melalui pembentukan Satgas PPLN dan kolaborasi dengan badan internasional, Indonesia menunjukkan komitmen terhadap prinsip-prinsip kemanusiaan, meskipun dalam batasan kerangka hukum dan ekonominya. Studi ini menyimpulkan bahwa pendekatan Indonesia memberikan kontribusi pada diskursus global tentang manajemen pengungsi dengan menunjukkan contoh bagaimana negara dapat terlibat dalam perlindungan pengungsi tanpa terikat oleh hukum konvensi pengungsi internasional. Hal ini menyoroti pentingnya inisiatif lokal dan kerja sama internasional dalam mengatasi kebutuhan pengungsi dan menyarankan kebutuhan untuk kebijakan yang lebih inklusif yang memfasilitasi integrasi sosial dan ekonomi pengungsi. Implikasi praktis meliputi rekomendasi untuk peningkatan mekanisme pengawasan dan penyelidikan guna mencegah eksploitasi pengungsi oleh sindikat penyelundupan dan penyebaran informasi hukum kepada pengungsi untuk mengurangi masuk dan tinggal secara tidak sah. Kata kunci: imigrasi, kolaborasi pemerintahan, pengungsi, UNHCR